2019
DOI: 10.1155/2019/5936940
|View full text |Cite
|
Sign up to set email alerts
|

How Does Overconfidence Affect Decision Making of the Green Product Manufacturer?

Abstract: Overconfidence is a universal and prevalent cognitive bias affecting decision making in operation management. In this paper, overconfidence is defined as a cognitive bias in which decision makers overestimate the accuracy of demand forecasting or (and) the demand itself. We call these two behaviors overprecision and overestimation, respectively. In order to explore how overconfidence affects decision making of the green product manufacturer, we build the demand function based on the manufacturer’s overconfiden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…However, in low-carbon supply chains, overconfidence can also affect the amount of money firms invest in R&D for emission reduction. Studies by Liu [47] and From Figures 4 and 5, one can see that, in all three scenarios, the product emission reduction rate, market demand and supply chain members' profits are inversely proportional to the manufacturer's emission reduction costs coefficient. In addition, the impact of manufacturers' overconfidence on supply chain members will gradually decrease as the emission reduction costs increase.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…However, in low-carbon supply chains, overconfidence can also affect the amount of money firms invest in R&D for emission reduction. Studies by Liu [47] and From Figures 4 and 5, one can see that, in all three scenarios, the product emission reduction rate, market demand and supply chain members' profits are inversely proportional to the manufacturer's emission reduction costs coefficient. In addition, the impact of manufacturers' overconfidence on supply chain members will gradually decrease as the emission reduction costs increase.…”
Section: Discussionmentioning
confidence: 90%
“…However, in low-carbon supply chains, overconfidence can also affect the amount of money firms invest in R&D for emission reduction. Studies by Liu [47] and Lu [48] et al concluded that overconfidence can lead to greener, low-carbon products, but at the same time can lead to higher costs and less profitability for firms [42]. This paper constructs a supply chain system with one retailer and one manufacturer and introduces the behavioral characteristics of manufacturer overconfidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the manufacturer sometimes exhibits overconfidence behaviour, i.e., the manufacturer anticipates more market demand than actual. For instance, the world's largest manufacturer of polysilicon wafers, Jiang Xi Saiwei LDK Solar Energy High Tech Co LTD., producing photovoltaic products, was bankrupted with loans of 20 billion RMB from 14 banks due to excessive stocking (over-estimation of demand) [26]. Zhou et al [51] defined manufacturers' overconfidence as a belief bias that they overestimate the impact of product greenness on demand and the accuracy of demand uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…Many countries and regions have successively issued relevant energy-saving and environmental protection laws and regulations, prompting enterprises to attach importance to green production ( Hamedirostami et al, 2021 ; Do et al, 2020 ). For example, in 2006, the European Union began to implement the “Directive on the Restriction of the Use of Certain Hazardous Substances in Electrical and Electronic Equipment” ( Jiang et al, 2019 ; So and Xu, 2016 ; Liu et al, 2019 ). In 2013, China issued the “Interpretation of the Supreme People's Court and the Supreme People's Procuratorate on Several Issues Concerning the Application of Law in the Handling of Environmental Pollution Criminal Cases” ( van Rooij, 2010 ).…”
Section: Introductionmentioning
confidence: 99%